6th International Conference on the Development of Biomedical Engineering in Vietnam (BME6) - Vo Van, Toi.; Nguyen Le, Thanh An.; Nguyen Duc, Thang; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
Under the motto "Healthcare Technology for Developing Countries" this book publishes many topics which are crucial for the health care systems in upcoming countries. The topics include Cyber Medical Systems Medical Instrumentation Nanomedicine and Drug Delivery Systems Public Health Entrepreneurship This proceedings volume offers the scientific results of the 6th International Conference on the Development of Biomedical Engineering in Vietnam, held in June 2016 at Ho Chi Minh City.
Microstructure Characterization of Cancellous Bone Based on Ultrasonic C-Scan Imaging -- Design of a Fluorescence Camera for Detection of Dental Caries -- Coded Excitation of the Fundamental Flexural Guided Wave in Coated Bone Phantoms -- A Principle of Adaptively Grouping Frames on Lossless Medical Video Compression Using Ideal Cross-Point Regions -- Analysis on MET Value due to the Relation between Echocardiogram (ECG) Signal and Human Physical Activities --  Accurate Characterization of Ultrasonic Guided Waves Propagating in Cortical Bone Acquired by a Single Transmitter-Receiver Pair Using Adaptive Signal Processing -- M-Sequence Excitation of Ultrasonic Backscatter Signals for Cancellous Bone Evaluation -- Development of a Real-time Supported System for Firefighters in Emergency Cases -- Coded Excitation of Guided Ultrasonic Waves in Long Bone for Assessment of Fracture Depth -- A Convenient Mouse Model of Myocardial Infarction for Developing Countries.  .
Keywords: Biomedical engineering; Biomedical Engineering and Bioengineering